2008
DOI: 10.1002/jmri.21050
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma treated with radio frequency ablation: An early evaluation with magnetic resonance imaging

Abstract: Purpose:To determine the usefulness of nonenhanced T1-weighted spoiled gradient-recalled acquisition in the steady-state (SPGR) MRI in the early assessment of the efficacy of radio frequency (RF) therapy for hepatocellular carcinoma (HCC). Materials and Methods:A total of 23 patients with 28 HCC nodules treated with percutaneous RF ablation underwent nonenhanced MRI within two days after the RF procedure and contrast-enhanced computed tomography (CT) one week after. MR assessment of ablation efficacy according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…MRI evaluation of the absence of tumor enhancement and the safety margin is also based on a visual comparison of the pre-and post-RFA images by referring to specific landmarks of the liver. A hyperintense zone on non-enhanced T1WI within 2 days after RFA reflects the extent of the ablated region [50]. Functional imaging including diffusion-weighted MRI has the ability to provide unique insights into molecular water distribution within a tumor, and therefore indicate tumor viability at a cellular level [51].…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…MRI evaluation of the absence of tumor enhancement and the safety margin is also based on a visual comparison of the pre-and post-RFA images by referring to specific landmarks of the liver. A hyperintense zone on non-enhanced T1WI within 2 days after RFA reflects the extent of the ablated region [50]. Functional imaging including diffusion-weighted MRI has the ability to provide unique insights into molecular water distribution within a tumor, and therefore indicate tumor viability at a cellular level [51].…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…In many studies for evaluating thermal ablation at the acute phase, MR images are acquired several days after treatment. 22 In our case, however, MR images were acquired within 2 hours after treatment, so tissue responses to ablation may be slight and MR ndings may diŠer from those in other studies. The groups of Lee 23 and Onishi 24 also reported MR images of the liver in animal models from 2 hours after radiofrequency (RF) ablation.…”
Section: Discussionmentioning
confidence: 68%
“…Regarding an early evaluation with MRI after RF ablation, Khankan et al . reported that a hyperintense zone on non‐enhanced T 1 ‐weighted MRI within 2 days after ablation reflected the extent of the ablated region 16 . Accordingly, blurring of the hyperintense rim on T 1 ‐weighted images can be attributed to a hemorrhage or a proteinaceous material within the ablated area 17,18 .…”
Section: Discussionmentioning
confidence: 99%